ANALISIS KUALITAS PRODUK, PELAYANAN DAN BRAND IMAGE TERHADAP MINAT KONSUMEN PADA PO. ROSALIA INDAH - Wibi Febrian; Burhanudin Ahmad Yani; Ratna Damayanti (JURNAL ILMIAH EDUNOMIKA, 2020)
This study aims to determine the effect partially and simultaneously product quality, service and brand image on consumer interest in PO. Rosalia Indah. This type of research uses quantitative methods. The population in this study was conducted on 100 respondents spread across the Solo Raya area, namely Solo, Sukoharjo, Karanganyar, Sragen, Wonogiri, Klaten and Boyolali. The sampling technique used in this study was purposive sampling technique. The analytical method used is multiple linear regression, data collection methods by distributing questionnaires. The results of this study indicate a simultaneous and significant effect of product quality, service and brand image on consumer interest in PO. Rosalia Indah with a value of Fcount ≥ Ftable (90.065 ≥ 2.70) and a significance of 0.000 ≤ 0.05. Partially product quality and brand image have a positive and significant effect on consumer interest with ttable value ≤ tcount (1.984 ≤ 4.311) on product quality and ttable value ≤ tcount (1.984 ≤ 2.576) on brand image, while for service variables, ttable value ≤ tcount ( 1,984 ≥ 1,094) and a significance value of 0.277 ≥ 0.05 so that the service variable does not have a positive effect on consumer interest in PO. Rosalia Indah. Keywords: Product Quality, Service, Brand Image and Consumer Interest